Assessing and Improving Documentation of Pediatric Brain Death Determination within an Electronic Health Record - Krawiec, Conrad; Ceneviva, Gary D.; Thomas, Neal J. (Neuropediatrics, 2019)
Background/Objective Pediatric brain death determination (BDD) can be subject to interprovider variability of documentation, resulting in diagnosis credibility. The aim of this study was to describe our approach to assessing pediatric BDD documentation and documentation variation in the electronic health record (EHR).Methods This was a single institution cross-sectional review of pediatric patients younger than 18 years determined to meet brain death criteria. We assessed electronic documentation and evaluated for the presence of contributing factors that can interfere with the brain death documentation based on our institutional brain death evaluation policy (core body temperature, systolic blood pressure within an acceptable range, sedative/analgesic drug effects, and neuromuscular blockade).Results In total, 33 pediatric brain death patients were identified. This review revealed pediatric BDD documentation consistency (n, %) as follows: performance of the first pediatric brain death clinical examination with temperature above 36°C (27, 81.8%), systolic blood pressure above the defined range (29, 87.9%), more than 24 hours following admission (28, 84.8%); performance of the second pediatric brain death clinical examination with temperature above 36°C (32, 97%), more than 12 hours following the first examination (26, 89.7%); and ensuring sedative infusions were discontinued within the recommended cutoff period prior to pediatric BDD (28, 84.8%). Clinical neurologic examinations were fully documented.Conclusions Pediatric BDD is a rare process subject to documentation omissions and error. Our findings highlight the variability of pediatric BDD electronic documentation among different providers and specialties at our institution. An approach to improving pediatric BDD documentation may start with completing a standardized electronic brain death document.
Keywords: critical care; electronic health record; intensive care unit; patient care; pediatric brain death